The Impact of Financial Reporting on Investor Decision Making - Edgar Eriazali Kasibe (Uganda Christian University, 2023)
The study was to establish the relationship between financial reporting and Investor decision making. The study was underpinned by the agency theory and stakeholder theory. The objectives were to find out the relationship between reliability of financial reports and decision making, to find out the relationship between timeliness of financial reports and decision making and, to find out the relationship between understandability of financial reports and decision making. The study took on the cross-sectional case study design where both qualitative and quantitative methods approaches were used to collect and analyze data. The targeted study population was 50 out of which a sample of 44 was selected using purposive and random sampling techniques. A total of 38 responses were got (86.4% response rate). Data was collected using the questionnaires and analyzed using Statistical Package for Social Scientists (SPSS) and content and thematic analysis for quantitative and qualitative data respectively. The findings revealed that there is a significant relationship between timeliness of financial reports and decision making, and a strong significant relationship between understandability and decision making. The study however revealed that there is an insignificant relationship between reliability of financial reports and decision making. The study concluded that timeliness and understandability of financial reports have a direct linkage with decision making. The study recommends that for the investors to improve in decision making there is need to have timely and understandable financial reports. The study further recommends that the investors should be trained to acquire necessary skills to help understand the financial reports so they make informed decisions
This is a dissertation.